2021
DOI: 10.3390/diagnostics11040716
|View full text |Cite
|
Sign up to set email alerts
|

Using Dynamic Features for Automatic Cervical Precancer Detection

Abstract: Cervical cancer remains a major public health concern in developing countries due to financial and human resource constraints. Visual inspection with acetic acid (VIA) of the cervix was widely promoted and routinely used as a low-cost primary screening test in low- and middle-income countries. It can be performed by a variety of health workers and the result is immediate. VIA provides a transient whitening effect which appears and disappears differently in precancerous and cancerous lesions, as compared to ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Furthermore, we expect the described trial to confirm that the mean accuracy, precision, sensitivity and specificity of the AVC test outperforms human assessment of VIA, as shown in our preliminary results [ 15 ]. Evidence should be found that the AVC test allows a reliable automation of cervical precancer and cancer detection.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, we expect the described trial to confirm that the mean accuracy, precision, sensitivity and specificity of the AVC test outperforms human assessment of VIA, as shown in our preliminary results [ 15 ]. Evidence should be found that the AVC test allows a reliable automation of cervical precancer and cancer detection.…”
Section: Discussionsupporting
confidence: 67%
“…Then, the contours of the lesions are obtained, delimitating all predicted lesions. The size of the lesions is compared to a predefined threshold (450 pixels) to decide whether the patient is negative or positive [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bae et al developed a smartphone-based endoscope that acquires and classifies images before and after application of the acetic acid [ 45 ]. Finally, Viñals et al developed an AI algorithm based on smartphone images without any additional component [ 46 ]. In the near future, smartphone mHealth and automated visual evaluations may allow for the automated and accurate detections of CIN and become key elements in cervical cancer screenings.…”
Section: Artificial Intelligence: a Vision Of The Futurementioning
confidence: 99%
“…In 2021, Roser et al. ( 15 ) proposed using PCA to reduce the dimensionality of the RGB vector and used an ANN to generate the probability map of the precancerous lesion for each pixel. Then, seed point region growth was used to connect the points exceeding the threshold value to the segment region, and whether HSIL+ was determined according to the size of the lesion region, but HSIL+ had nothing to do with the size of the region.…”
Section: Related Workmentioning
confidence: 99%